(untitled) (Shanti Journal, 2023)
Mongolian National Calligraphy is one of the Intangible Cultural Heritages in Need of Urgent Safeguarding of Mongolia that is registered in UNESCO and claimed as a valuable heritage in the project “Mongolian Values”. Therefore, increasing the use of calligraphy is very crucial for maintaining cultural immunity. The research was focused on determining the modern use of Mongolian Calligraphy based on the historical development and its contemporary situation. The data were collected from 300 respondents as general, casual and key informants through questionnaires and in-depth interviews. The questionnaire result has been analyzed both in the SPSS program and in MS Excel Formula Section and confirmed by the experts in linguistics. The final result was interpreted based on the descriptive method. The research result suggested that Mongolian National Calligraphy should be studied at the scientific level and disseminated in public. Therefore, there is a need to integrate multilateral cooperation into a common policy in order to surge the further use of Mongolian National Calligraphy.